The love-hate relationship between Ras and Notch. - Sundaram, M.V. (Genes & Development, 2005)
The Ras and Notch signaling pathways are used over and over again during development to control many different biological processes. Frequently, these two signaling pathways intersect to influence common processes, but sometimes they cooperate and sometimes they antagonize each other. The Caenorhabditis elegans vulva and the Drosophila eye are two classic paradigms for understanding how Ras and Notch affect cell fates, and how the two pathways work together to control biological pattern. Recent advances in these systems reveal some of the mechanisms by which Ras and Notch can interact. Similar types of interactions in mammals may be important for determining whether and how alterations in Ras or Notch lead to cancer.